Perda de grãos de arroz decorrentes do transporte rodoviário no município de Itaqui/RS - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The transport of rice grains, through the highways, plays a fundamental role in the logistics process in the producing regions, considering from the exit of the crop to the final destination, but the system provides a considerable loss of grain along the route. The present study had the objective of identifying and quantifying the losses of rice grains resulting from the process of road transport from the property to the grain receiving unit. The experiment was carried out in the municipality of Itaqui-RS, located in the western border of the state of Rio Grande do Sul, during the harvest period of the 2016/2017 crop. The work had as analysis items, ten road transport vehicles, being (trucks with wooden body and trucks with metal body denominated Roll on / Roll off), in routes with different distances (37 and 103 km), both contemplating And unpaved sections. The obtained results showed that the losses in grain transport are directly proportional to the distances traveled, they can differ in relation to the type of vehicle used and the route traveled. The vehicles with wood body showed higher percentage losses per ton of grain transported in relation to vehicles with Roll on / Roll off system in the unpaved route of the longest route, but did not differ in the shortest route. Therefore, grain losses in road transport are caused due to vehicles in poor conditions, roads in bad conditions and the lack of awareness of all those involved in the process.
Keywords: Perda de grãos; Arroz; Transporte rodoviário; Loss of grains; Rice; Road transport; CNPQ::CIENCIAS AGRARIAS